(3LQGFe GdJgQjH (B:s (3aj VhA Gdabg h GdGFMI GdJfajPjI h JYdjeGJ GdfjGHI h GdbjhO h GdChUGa h CMcGe GdfbV h GdOSJhQjI GdYdjG (B: (3GdJgQjH GdLeQcj bGfhf (B22(3dSfI (B1963 (3GdeYOd HGdbGfhf (B14 (3dSfI (B2004 : (3JgQjH GdJHZ h JgQjH GdfbO (B/s - (3gQLI, eUWai eLOjs ((3GdefUhQI(B: s (3OGQ GdacQ hGdbGfhf(B, s, 2005)
(3GdJgQjH GdLeQcj HGdJWQb Gdi fUhU GdbGfhf Qbe (B66 (3dSfI (B1963 (3HGUOGQ bGfhf GdLeGQc GdeYOd HGdbGfhf (B14 (3dSfI (B2004 (3aj (B22(3CHQjd (B2004 (3, bQGQ Qbe (B765 (3dSfI (B2001 (3HTCf JMOjO bjeI GdHVGFY ddCEQGV GdLeQcjI , GdePcQI GdGjVGMjI deTQhY bQGQ QFjS GdLeghQjI HGdbGfhf (B66 (3dSfI (B1963 (3HGUOGQ bGfhf GdLeGQc , ef GMcGe GdeMceI GdOSJhQjI GdYdjG , GdbjhO h GdGhUGa , ef GMcGe eMceI GdfbV , HGH eQJHW ef bVGjG GdLeGQc aj eSGFd eJfhYI ceG Je JfGhd JgQjH GdJHZ HGdJWQb Gdi fUhU GdbGfhf Qbe (B92 (3dSfI (B1964 (3aj TCf JgQjH GdJHZ , GdbjhO h GdGhUGa , ef GdJYdjeGJ GdYGeI ddfjGHGJ , ef CMcGe eMceI GdfbV h cPG JfGhd JgQjH GdfbO HGdJWQb Gdi fUhU GdbGfhf Qbe (B38 (3dSfI (B1994 (3HJfXje GdJYGed HGdfbO GdGLfHj GdeYOd h JbQjQ GddLfI GdeTJQcI h GdePcQI GdGjVGMjI h JbQjQ dLfI GdTDhf GdGbJUGOjI Yf eTQhY bGfhf HEdZGA GdeGOI (B3 (3ef GdbGfhf Qbe (B38 (3dSfI (B1994 (3h GdePcQI GdGjVGMjI HTCf GdJYOjd SGda GdPcQ h bQGQ hRjQ GdGbJUGO Qbe (B295 (3dSfI (B1994 (3HJfajP CMcGe GdbGfhf Qbe (B38 (3dSfI (B1994 (3h bQGQ hRjQ GdGbJUGO Qbe (B331 (3dSfI (B1994 (3HGUOGQ GddGFMI GdJfajPjI h bQGQ hRjQ GdGbJUGO Qbe (B103 (3dSfI (B2001 (3HJYOjd HYV CMcGe GddGFMI GdJfajPjI h GdbjhO h GdChUGa h HYV GdJYdjeGJ GdYGeI ddfjGHI h CNjQG JYdjbGJ h CMcGe (B. s
Keywords: (3GdLQGFe GdGbJUGOjIs; (3GdQShe GdLeQcjI (B- (3JgQHs; (3JgQH GdHVGFYs